OP0241 Autotaxin is Over-Expressed in Systemic Sclerosis (SSC) Skin, Mediates Bleomycin-Induced Dermal Fibrosis via IL-6, and is A Target for SSC Therapy. (10th June 2014) - Castelino, F.V.; George, L.M.; Bain, G.; Goulet, L.; Lafyatis, R.; Tager, A.M.
Abstract : Background: Autotaxin (ATX) is an enzyme present in biological fluids that is responsible for the production of the lipid mediator, lysophosphatidic acid (LPA). We previously implicated LPA and its receptor, LPA1 in SSc pathogenesis, an autoimmune disease characterized by progressive fibrosis that is refractory to current therapies. 1 Here we studied the role of ATX in SSc dermal fibrosis using the bleomycin mouse model and skin biopsy samples from SSc patients and healthy controls. We evaluated the role of IL-6, a cytokine implicated in SSc, in mediating ATX-induced fibrosis. Additionally, we investigated the therapeutic potential of targeting ATX, by using a novel ATX inhibitor, PAT-048 in this model. Objectives: To investigate the role of ATX in SSc dermal fibrosis utilizing the bleomycin mouse model of dermal fibrosis and skin samples from SSc patients and healthy controls. Methods: Bleomycin or saline was administered subcutaneously to C57Bl/6 mice daily for 3, 7, 14 and 28 days. 6mm dermal punch biopsies were obtained. ATX levels in homogenized skin were measured by qPCR and ELISA. The effect of ATX inhibition with PAT-048 (20mg/kg by oral gavage daily) was measured in the model after 28 days. Dermal thickness was measured using H&E-stained sections. Collagen was visualized by Masson's trichrome stain, and quantified by hydroxyproline measurement. Plasma ATX activity was measured and skin IL-6 expression was evaluated by immunohistochemistry (IHC). To evaluate the role of IL-6 in vitro, the effect of LPA-induced ATX expression was tested on human dermal fibroblasts transfected with IL-6 siRNA. Skin ATX expression was additionally measured in diffuse SSc patients and healthy controls by qPCR, and IL-6 expression was evaluated by IHC. Results: ATX expression at both the mRNA and protein level was increased at Day 3 after bleomycin injection (3-fold increase, p=0.06 ) suggesting a role for ATX early in fibrosis. Treatment with PAT-048 attenuated bleomycin-induced dermal fibrosis at Day 28 (50% reduction, p=0.07 ), and reduced IL-6 expression in the dermis. In vitro studies of human dermal fibroblasts showed that LPA-induced ATX expression was attenuated with siRNA knock-down of IL-6 (65% reduction, p=0.005) . Furthermore, ATX expression was increased in SSc skin (n=7) compared to healthy controls (n=5; 3-fold increase, p=0.006 ) and IL-6 expression by IHC was increased in SSc skin compared to healthy controls (n=3 per group). Conclusions: We demonstrate that ATX is an important regulator of LPA signaling and has a role in early SSc fibrosis. Pharmacologic inhibition of ATX with a novel ATX inhibitor, PAT-048 attenuated dermal fibrosis and IL-6 expression. Knock-down of IL-6 in fibroblasts in vitro abrogated LPA-induced ATX expression, suggesting an autocrine loop for LPA/ATX/IL-6 signaling. Extension of studies to humans showed both ATX and IL-6 are increased in SSc skin compared to healthy controls. Targeting ATX may thus be an effective new therapeutic strategy for SSc fibrosis. References: Castelino FV et al. Amelioration of dermal fibrosis by genetic deletion or pharmacologic antagonism of lysophosphatidic acid receptor 1 in a mouse model of scleroderma. Arth Rheum, 2011; 63(5):1405-15. Disclosure of Interest: F. Castelino: None declared, L. George: None declared, G. Bain Employee of: PharmAkea, L. Goulet Employee of: PharmAkea, R. Lafyatis: None declared, A. Tager: None declared DOI: 10.1136/annrheumdis-2014-eular.2979